The grammar of the 14th century melody: tonal organization and compositional process in the chansons of Guillaume de Machaut and the Ars Subtilior - Plumley, Yolanda (New York and London Garland Publishing, 1996)
By comparing the songs of Marchaut with a later collection from the Chantilly codes, both large repertories, explores how the growing complexity of musical language affected the fundamental way in which 14-century composers organized their musical material. Examines patterns in the structural organ.